Purification, Characterization and in vitro Evaluation of Polymyxin A From Paenibacillus dendritiformis: An Underexplored Member of the Polymyxin Family - Jangra, Manoj; Randhawa, Harmandeep Kaur; Kaur, Manpreet; Srivastava, Anugya; Maurya, Navdezda; Patil, Prashant P.; Jaswal, Pallavi; Arora, Ashish; Patil, Prabhu B.; Raje, Manoj; Nandanwar, Hemraj (Frontiers in Microbiology, 2018)
Nosocomial infections caused by antibiotic-resistant Gram-negative pathogens are of grave concern today. Polymyxins are considered as the last resorts of therapy to treat these multi-drug resistant bacteria. But their associated nephrotoxicity and neurotoxicity calls for the development of safer polymyxin therapy until novel and less toxic antibiotics are discovered. No other polymyxin molecule except polymyxin B and E (colistin) is explored thoroughly in literature to demonstrate its clinical relevance. In the present study, we have isolated two antimicrobial compounds named P1 and P2, which we later identified as polymyxin A2 and A1 respectively. We tested their minimum inhibitory concentrations (MICs) against multi-drug resistant clinical isolates, performed membrane permeabilization assays and determined their interaction with lipopolysaccharide (LPS). Finally, we studied their toxicity against human Leukemic monocyte cell line (THP-1) and embryonic kidney cell line (HEK 293). Both compounds displayed equal efficacy when compared with standard polymyxins. P1 was 2-4 fold more active in most of the clinical strains tested. Moreover, P1 showed higher affinity towards LPS. In cytotoxicity studies, P1 had IC50 value (>1000 µg/ml) similar to colistin against HEK cells but immune cells i.e. THP-1 cell lines were more sensitive to polymyxins. P1 showed less toxicity in THP-1 cell line than all other polymyxins checked. To sum up, P1 (polymyxin A2) possessed better efficacy than polymyxin B and E and had least toxicity to immune cells. This compound should be further investigated for its in vivo efficacy & toxicity to develop it as a drug candidate.